O-GlcNAcylation is crucial for sympathetic neuron development, maintenance, functionality and contributes to peripheral neuropathy - Wu, Hsueh-Fu; Huang, Chia-Wei; Art, Jennifer; Liu, Hong-Xiang; Hart, Gerald W.; Zeltner, Nadja (Frontiers in Neuroscience, 2023)
O-GlcNAcylation is a post-translational modification (PTM) that regulates a wide range of cellular functions and has been associated with multiple metabolic diseases in various organs. The sympathetic nervous system (SNS) is the efferent portion of the autonomic nervous system that regulates metabolism of almost all organs in the body. How much the development and functionality of the SNS are influenced by O-GlcNAcylation, as well as how such regulation could contribute to sympathetic neuron (symN)-related neuropathy in diseased states, remains unknown. Here, we assessed the level of protein O-GlcNAcylation at various stages of symN development, using a human pluripotent stem cell (hPSC)-based symN differentiation paradigm. We found that pharmacological disruption of O-GlcNAcylation impaired both the growth and survival of hPSC-derived symNs. In the high glucose condition that mimics hyperglycemia, hPSC-derived symNs were hyperactive, and their regenerative capacity was impaired, which resembled typical neuronal defects in patients and animal models of diabetes mellitus. Using this model of sympathetic neuropathy, we discovered that O-GlcNAcylation increased in symNs under high glucose, which lead to hyperactivity. Pharmacological inhibition of O-GlcNAcylation rescued high glucose-induced symN hyperactivity and cell stress. This framework provides the first insight into the roles of O-GlcNAcylation in both healthy and diseased human symNs and may be used as a platform for therapeutic studies.